Process plant layout - Moran, Sean (Elswevier, BH, 2017)
"Mecklenburgh's Process Plant Layout 2nd Edition is an in depth guide which begins with general fundamentals and then becomes progressively more detailed; the same progression followed by process designs. It explains how to lay out process equipment and piping relative to each other and to environmental features in a safe, economical way. It is supported with tables of separation distances, rules of thumb, and descriptions of design stage reviews. Sean Moran has thoroughly re-written this book to reflect advances in technology and best practice; for example changes in how designers balance layout density with cost, operability and safety considerations. The content covers the 'why' underlying process design company guidelines, and understanding this will provide a firm foundation for career growth for process design engineers. Process plant designers in contracting, consultancy, and operating companies at all stages of their careers are the primary audience for this book. The work is also of importance for operations and maintenance staff involved with a new build, to guide them through the plot plan reviews. Project engineers, plant and project managers will also find the work of great interest. It is written in a style suitable for use as a student textbook, as well as a reference for graduate engineers."--Resumé vydavatele